Orientação informacional em instituições de ensino superior de Belo Horizonte - Solange Madalena Souza Macedo (2011)
The study describes how managers of private Higher Education Institutions (HEIs) realize the forms that how the organizations that they work have capacities connected to efficient use of the information, here described as Orientation Informational (OI). The theoretical base of this study was the Model of DI by Donald A. Marchand, William J. Kettinger and John D. Rollins (2000). This Model takes the practices as central elements of management of the information, values and behaviors informational and practices in information technology. The data collection was carried out through questionnaires sent to the managers of the HEIs, which 83 totalizing answered. The data were analysed through descriptive statistics, as well as tests of differences between averages. The results demonstrate that the HEIs are orientated to the information, sometimes with more expression in some of the dimensions of each approach of OI now with less expressiveness. It was noticed that the managers of the HEIs realize each one of the practices, as well as the values and behaviors informational, when there are in these organizations high degrees of existences of the component practices of OI, though it is still on this side of what an orientated direction informational, from the point of view of the authors of the model. Between three capacities that the precise organization to be orientated to informational, there was a predominance in the HEIs of the Practices in Information Technology to reach the objectives.